ASSOCIATION OF RISK FACTORS WITH PREVALENCE OF GESTATIONAL DIABETES MELLITUS - SHAIKH, MOHAMMED NADEEM; STANLEY, HELOISE; SINGLA, DISHA; ARORA, SMRITI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Gestational diabetes mellitus (GDM) is among the most common complications of pregnancy associated with adverse maternal and perinatal outcomes. There is an increased risk of gestational hypertension, preeclampsia, and operative delivery and their associated potential morbidities in women with GDM, especially in India, with increasing obesity, lifestyle, and dietary changes. Hence, this study was undertaken to study the prevalence of GDM and evaluate its maternal and neonatal outcomes. Methods: This study was conducted on 200 pregnant women between 26 and 28 weeks of gestation who were screened for GDM and diagnosed to have GDM based on WHO criteria. Risk factors associated with GDM and neonatal complications were studied. Results: Most of the GDM cases were significantly associated with body mass index (BMI) >25 kg/m2, family history of diabetes, previous macrosomia/ large for gestational age (LGA) babies, and history of GDM with p<0.001. The incidence of preeclampsia and polyhydramnios was significantly higher among GDM cases. Operative delivery and assisted (forceps) delivery had a strongly significant association with GDM (p<0.001). Hypoglycemia was the most common complication noted in neonates of GDM women. The incidence of complications was also significantly higher among neonates born with GDM. Conclusion: Our study concluded that BMI, family history of diabetes, past GDM, and previous LGA babies were important risk factors for GDM. The study emphasizes the need to screen all pregnant women for GDM so that timely diagnosis and intervention will reduce both maternal and perinatal complications.